Aesthetic Study on Sakucing's Instagram Channel as an Educational Media for Teenagers - Reza Trisnawati, Rossalia; Sugiarto, Eko (Universitas Negeri Semarang, 2024)
Cats are one of the most desirable animals to keep because of their cuteness. To get them, people usually buy them from pet shops, animal breeders, or adoption. However, not everyone who keeps them pays attention to the responsibilities and risks involved in keeping them. Many abandoned cats posted on social media show the lack of awareness and information on animal welfare. Instagram provides an opportunity to deliver these messages effectively and creatively as it is one of the most popular social media platforms in Indonesia. The discussion of visual aesthetics studies is used to deepen the understanding of how visual elements affect perception and interpretation. In this digital age, where visuals play an important role in communication, understanding aesthetics becomes relevant as it is able to make information more attractive and easy to understand. This research aims to explain the aesthetics and messages contained in Sakucing.id's Instagram content. This research uses descriptive qualitative methods. Data collection techniques were obtained by documenting literature data, artwork data, and content information data. Data analysis is done by analyzing the visual and content analysis of the content, then studying it using Fledman's aesthetic theory. The results show that the visualization of Sakucing content illustrations interprets the invitation to care more about cats by expressing it using a cartoon style as a visual appeal aimed at teenagers.